CEU Graduation Ceremony 2000 - Soros - Göncz
The presentation of the Central European University Open Society Prize to Hungarian President Árpád Göncz by CEU Founder and Chairman of the Board of Trustees George Soros during the graduation ceremony of the class of 1999/2000. Contains President Árpád Göncz’s acceptance speech.